Enantioselective Rhodium‐Catalyzed Coupling of Arylboronic Acids, 1, 3‐Enynes, and Imines by Alkenyl‐to‐Allyl 1, 4‐Rhodium(I) Migration. (24th November 2017) - Callingham, Michael; Partridge, Benjamin M.; Lewis, William; Lam, Hon Wai
Abstract: A chiral rhodium complex catalyzes the highly enantioselective coupling of arylboronic acids, 1, 3‐enynes, and imines to give homoallylic sulfamates. The key step is the generation of allylrhodium(I) species by alkenyl‐to‐allyl 1, 4‐rhodium(I) migration.